PERANCANGAN BOOTH DESAIN SEMANIS COKLAT GONDANGREJO KARANGANYAR - Suryono (JURNAL KEMADHA, 2021)
ABSTRACTSemanis Coklat is a beverage business in Gondangrejo and has become a favourite drink of today's society. Semanis Coklat was sold since 2019 and was visited by many buyers in Gondangrejo. Booth design is a creative design that links form, structure, material, colour, image, typography and design elements with product information to market the product. Booth Design is used to make the appearance of the booth that is used for selling to make it more attractive. Branding is the giving of a name, term, sign, symbol, design, or a combination of these, which aims to identify the goods or services or groups of sellers and differentiate them from those of competitors. Semanis Coklat has good taste and chocolate, but Semanis Coklat 's booth design doesn't support it because they still use ordinary tables to sell and look less attractive since they look messy, can damage the attractiveness and are uncomfortable. Making Booth Design is expected to be more attractive and has particular value to consumers. The design method starts with thinking about ideas for designing, conducting a survey with Semanis Coklat to take product photos, conducting a brief by collecting data from observations, conducting brainstorming, which is an effort to develop ideas in consultation with the supervisor, conducting a creative brief to produce designs that are in accordance with the background, and perform visualization work from pre-determined creative ideas.Keywords: Semanis Coklat, Booth Design, Design, Promotion.